SEISMIC STRATIGRAPHY OF LATE QUATERNARY DEPOSITS FROM THE SOUTHWESTERN BLACK SEA SHELF: EVIDENCE FOR NON-CATASTROPHIC VARIATIONS IN SEA-LEVEL DURING THE LAST ~10 000 YR - Aksu A.E.; Hiscott R.N.; Işler F.I.; Marsh S.; Yaşar D. (My University, 2002)
Detailed interpretation of single channel seismic reflection and Huntec deep-tow boomer and sparker profiles demonstrates that the southwestern Black Sea shelf formed by a protracted shelf-edge progradation since the Miocene–Pliocene. Five seismic–stratigraphic units are recognized. Unit 1 represents the last phase of the progradational history, and was deposited during the last glacial lowstand and Holocene. It is divided into four subunits: Subunit 1A is interpreted as a lowstand systems tract, 1B and 1C are interpreted as a transgressive systems tract, and Subunit 1D is interpreted as a highstand systems tract. The lowstand systems tract deposits consist of overlapping and seaward-prograding shelf-edge wedges deposited during the lowstand and the subsequent initial rise of sea level. These shelf-edge wedges are best developed along the westernmost and easternmost segments of the study area, off the mouths of rivers. The transgressive systems tract deposits consist of a set of shingled, shore-parallel, back-stepping parasequences, deposited during a phase of relatively rapid sea-level rise, and include a number of prograded sediment bodies (including barrier islands, beach deposits) and thin veneers of seismically transparent muds showing onlap onto the flanks of older sedimentary features. A number of radiocarbon dates from gravity cores show that the sedimentary architecture of Unit 1 contain a detailed sedimentary record for the post-glacial sea-level rise along the southwestern Black Sea shelf. These data do not support the catastrophic refilling of the Black Sea by waters from the Mediterranean Sea at 7.1 ka postulated by [Ryan, Pitman, Major, Shimkus, Maskalenko, Jones, Dimitrov, Görür, Sakınç, Yüce, Mar. Geol. 138 (1997) 119–126], [Ryan, Pitman, Touchstone Book (1999) 319 pp.], and [Ballard, Coleman, Rosenberg, Mar. Geol. 170 (2000) 253–261].
Keywords: Quaternary; Cenozoic::Quaternary; Кайнозой::Четвертичная